Unlocking Nutritional Potential: Enriched Barley In Functional Nutrition - I.R. Askarov; D.T. Khasanova (Zien Journals, 2024)
This article explores the significance of incorporating enriched food in Functional Nutrition, with a specific focus on the versatile applications of barley. It sheds light on the valuable aspects of harvested barley, emphasizing its nutritional benefits and potential contributions to a balanced diet. Furthermore, the article provides insights into the preparation and utilization of barley malt at home, offering practical guidance for individuals seeking to harness the nutritional richness of this grain. Additionally, recommendations are offered for maximizing the home use of harvested barley, empowering readers to integrate this nutritious ingredient into their culinary repertoire with confidence
Keywords: enriched food; biologically active additive; harvested barley